Problematizing hegemonic masculinity in soccer teaching/training: experience report in a social project lead by a student entity - Silva, Luis Felipe Nogueira (2021)
BACKGROUND: Sports practices are imbued with values, beliefs, and conceptions, which, devoid of pedagogical criticism, reinforce gender inequalities, such as those resulting from hegemonic masculinity. OBJECTIVE: To report an educational experience with a view to combating hegemonic masculinity in the sporting context, theoretically anchored by the tripod of references in Sport Pedagogy and Game Pedagogy. METHODS: The study is supported, methodologically, by a descriptive-exploratory perspective, by exposing pedagogical behaviors resulting from soccer classes in a social sports project, conducted by university students, in the city of Limeira (SP, Brasil). RESULTS: The adoption of didactic-methodological conducts, based on the Game’s Pedagogy, allowed the development of contents inherent to the teaching and learning of football that, when distancing themselves from traditional teaching concepts, and endowed with intentionalities, also fostered problematizations and awareness of issues dear to social justice, such as hegemonic masculinity. CONCLUSION: At the end of the report, actions and interventions from counter-hegemonic have political-pedagogical practices been activated, allowed the pedagogical frameworks of Game’s Pedagogy.